Development of a real-time PCR detection method for a FCGR2A polymorphism in the LightCycler and application in the heparin-induced thrombocytopenia syndrome - Kroupis, C.; Theodorou, M.; Kounavi,M.; Oliveira, S.C.; Iliopoulou,E.; Mavri-Vavayanni,M.; Melissari,E.N.; Degiannis, D. (Clin.Biochem., 2009)
OBJECTIVE: The FcgammaRIIa receptor is responsible for the activation of platelets by antibodies in heparin-induced thrombocytopenia (HIT). The c.497G>A polymorphism in the corresponding FCG2RA gene (H131R) has been implicated in the HIT syndrome and we aimed at its rapid and reliable determination. DESIGN AND METHODS: We designed a novel asymmetric real-time PCR method in the LightCycler that uses two hybridization probes and is followed by melting curve analysis. Seventy-one post-cardiac-surgery HIT Greek patients well ascertained by clinical data, immunological and functional tests (PAT, CD62P-selectin and microparticle flow cytometric detection) were studied, along with a clinically relevant group of 49 thrombocytopenic control patients and 119 healthy subjects. RESULTS: The developed method has excellent analytical characteristics (linear and efficient amplification, precision), has wide DeltaT(m) between the two alleles H and R (11.53 degrees C), and is in 100% concordance with validated controls and another commonly used screening method. The RR percentage increased from 10% in the control populations to 24% in the HIT patient group. CONCLUSION: The described method is technically simple, robust, fast, and accurate. A statistically significant difference was found in the comparison between the groups of HIT patients and healthy subjects [RR vs. RH+ HH, chi(2) test, p=0.01, OR (95% C.I.) 2.81 (1.21-4.68)]. The RR frequency in the Greek population was found to be the lowest among Caucasians
Keywords: Adverse effects; analysis; Base Sequence; chemically induced; DNA; genetics; Genotype; Greece; Heparin; Humans; methods; Molecular Sequence Data; polymerase chain reaction; Polymorphism,Genetic; Receptors,IgG; Thrombocytopenia